2011
DOI: 10.3892/ijo.2010.863
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor cures after Foscan photodynamic therapy combined with the ceramide analog LCL29. Evidence from mouse squamous cell carcinomas for sphingolipids as biomarkers of treatment response

Abstract: To improve anticancer therapeutic success of photodynamic therapy (PDT), combination treatments represent a viable strategy. Sphingolipid analogs combined with anticancer drugs can enhance tumor response. We have shown that LCL29, a C6-pyridinium ceramide, promotes therapeutic efficacy of Photofrin-PDT in mouse SCCVII squamous cell carcinoma tumors. The long-term effect of the combination PDT + LCL29 is unknown. In this study we used the same model to test the long-term curative potential of Foscan-PDT + LCL29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…Combining PDT with LCL29 is a novel approach, as there have been no reports of this combination, apart from our in vivo studies [11, 12]. The present study shows that enhanced, FB-sensitive mitochondrial ceramide accumulation correlates with enhanced mitochondrial apoptosis and cell killing after combining PDT and LCL29.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…Combining PDT with LCL29 is a novel approach, as there have been no reports of this combination, apart from our in vivo studies [11, 12]. The present study shows that enhanced, FB-sensitive mitochondrial ceramide accumulation correlates with enhanced mitochondrial apoptosis and cell killing after combining PDT and LCL29.…”
Section: Resultssupporting
confidence: 45%
“…1, panel A) [7], has been shown to act as an effective anticancer agent, alone or in combination with chemotherapy [5, 6, 9, 10]. We have shown in a syngeneic murine model of head and neck squamous cancer cell carcinoma (HNSCC) that combining PDT with LCL29 augments tumor-associated ceramide accumulation and apoptosis, as well as that the combination improves tumor response to PDT [1113]. A better understanding of the mechanisms of improved tumor response after the combination is warranted, in order to exploit them to enhance cancer cell killing.…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated the efficacy of one such agent, C6-ceramide analogue LCL29, as adjuvant to PDT. Our results show that cure rates of PDT-treated mouse squamous cell carcinomas SCCVII can be significantly increased by adjoined treatment with a single dose of LCL29 [11]. Further investigation revealed that the combined LCL29 treatment strongly amplified apoptosis in cancer cells of PDT-treated tumors [14].…”
Section: Introductionmentioning
confidence: 99%
“…ceramide, sphingosine and sphingosine-1-phosphate) are critical mediators of cellular stress responses and have prominent roles in cell apoptosis, autophagy, as well as immune cell functions [6-8]. Our earlier research has shown that SLs are important participants in response to PDT at both cellular and tumor levels [9-11]. Similar to chemotherapy and some other types of cancer therapy, PDT has a distinct signature effect on the SL profile owing in particular to induction of the de novo ceramide biosynthesis [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation